Left atrial appendage mechanical dispersion provides incremental value for thromboembolic risk stratification over CHA2DS2-VASc Score in nonvalvular atrial fibrillation. (15th May 2020) - Mao, Yankai; Ma, Mingming; Yang, Yuan; Yu, Chan; Wang, Yunhe; Jiang, Ruhong; Jiang, Chenyang
Abstract: Background: Left atrial appendage (LAA) dysfunction is associated with increased risk of thromboembolic events. However, little is known about LAA mechanical dispersion (MD) would provide additional information toward thromboembolism over the CHA2DS2-VASc score. The aim of this study was to determine the association of LAA mechanics as assessed by speckle-tracking imaging with thromboembolic events in patients with nonvalvular atrial fbrillation (AF). Methods: A total of 116 consecutive patients with AF referred for transesophageal echocardiography (TEE) were prospectively enrolled. Of these, 17(14.7%) patients had prior embolic events. Using speckle-tracking echocardiography (STE), we measured the LAA strain in each of 24 segments in mid-esophageal TEE views obtained at 0°, 45°, 90° and 135°. LAA MD was defined as the standard deviation (SD) of time to peak positive strain corrected by the R-R interval. Results: Patients with embolism had lower LAA global longitudinal strain (GLS) (8.56 ± 2.62% vs 11.37 ± 5.54%, p  = 0.002) and higher LAA MD (16.90 ± 6.67% vs 12.10 ± 3.94%; P  = 0.010) than those without embolism. LAA MD >13.1% differentiated patients with embolism from controls, with an area under the curve (AUC) of 0.709( p  = 0.004). LAA MD was independently associated with the presence of thromboembolism in multivariate analysis (odds ratio, 1.24; 95% confidence interval, 1.08–1.42; P  = 0.002). The model based on CHA2 DS2 -VASc score for discrimination of patients with embolism was significantly improved by adding LAA MD ( P  < 0.01). Conclusion: LAA MD obtained from strain echocardiography was significantly associated with a prior history of embolic events and had incremental diagnostic value over CHA2DS2VASc score, suggesting that LAA MD may be useful in refining thromboembolic risk stratification in patients with AF. Highlights: Patients with embolism had higher LAA mechanical dispersion (MD) than those without embolism. LAA MD was independently associated with the presence of thromboembolism in multivariate analysis. LAA MD significantly improved the model based on CHA2DS2-VASc score for discrimination of patients with embolism.